IMPLEMENTASI E-GOVERMENT SEBAGAI UPAYA PENINGKATAN POTENSI DESA DI DESA BUMIREJO MENGGUNAKAN WEB MOBILE - Eka Pratiwi; Muhamad Muslihudin (Jurnal TAM (Technology Acceptance Model), 2018)
In the current era of globalisai E-Government role is needed in the government system, because it can be used to facilitate the delivery of information and is expected to face changes in accordance with Law No. 11 Year 2008. Implementation of E-Government in an effort to increase the potential village in Bumirejo Village is wrong a website-shaped media, used in facilitating the dissemination of information and viewing Potential data as well as the state and government system in Bumirejo Village, the E-Government process of Bumirejo Village by analyzing an existing system using the SDLC method, the SDLC method passes through several the stage from start of this system is planned until the system is applied, then proceed with making some diagram that is diagaram ERD (Entity Relationship Diagram), Usecase system running and Relation table database, then proceed with designing Web-based website of Mobile and use pemograman  structured using PHP programming language and MySQL database.